Expresión xy⊕yz
El profesor se sorprenderá mucho al ver tu solución correcta😉
Solución
Solución detallada
(x∧y)⊕(y∧z)=y∧(x∨z)∧(¬x∨¬z)
y∧(x∨z)∧(¬x∨¬z)
Tabla de verdad
+---+---+---+--------+
| x | y | z | result |
+===+===+===+========+
| 0 | 0 | 0 | 0 |
+---+---+---+--------+
| 0 | 0 | 1 | 0 |
+---+---+---+--------+
| 0 | 1 | 0 | 0 |
+---+---+---+--------+
| 0 | 1 | 1 | 1 |
+---+---+---+--------+
| 1 | 0 | 0 | 0 |
+---+---+---+--------+
| 1 | 0 | 1 | 0 |
+---+---+---+--------+
| 1 | 1 | 0 | 1 |
+---+---+---+--------+
| 1 | 1 | 1 | 0 |
+---+---+---+--------+
(x∧y∧¬z)∨(y∧z∧¬x)
Ya está reducido a FNC
y∧(x∨z)∧(¬x∨¬z)
y∧(x∨z)∧(¬x∨¬z)
(x∧y∧¬x)∨(x∧y∧¬z)∨(y∧z∧¬x)∨(y∧z∧¬z)
(x∧y∧(¬x))∨(x∧y∧(¬z))∨(y∧z∧(¬x))∨(y∧z∧(¬z))